Post China 16 : Competition for Chinese exports - Lang, Vladimír (2016)
This thesis examines the evolution of China's economy and the competitive position of its exports in the international market. The thesis explores whether China is losing its competitive edge in export to the group of developing countries called Post China 16. First chapter identifies macroeconomic variables that significantly influence exports of a specific economy. Second chapter discusses the development of selected economic variables in Post China 16 economies. It studies whether the development of selected variables reveals possible changes in the competitive position of China and selected developing countries. Final part of the thesis develops an econometric model that tests the influence of selected variables on development of exports across several industries of The Post China 16 economies. Results confirm that most of the variables influence exports as the theory predicts and that the influence is higher in some industries than others. However, the model has limitations due to the shortcomings of the data.